Situación normativa de la Sociedad de la Información en Colombia - Salazar, Juan Fernando (2023)
This article aims to describe the laws that regulate two main Information Society issues in Colombia: (i) e-commerce, digital signatures and certification authorities, and (ii) elect ronic crimes and crimes committed by electronic means. In this sense, the Information Society is projected as a cross-border phenomenon, and legal solutions implemented in Colombia are compared with those of other re gions, as well as t hose promoted by international organizations. This analysis leads to the conclusion that a legal framework for the Information Society has to be based on the existence of long-term public policies, which do not run counter to the process of globalization.